Heavy Petting - Benz, Obie; Waletzky, Joshua; Sissel, Sandi; Taylor, Dyanna (New Video, 2007)
"Heavy Petting" is a hilarious and salacious exploration of the sexual mores of the 50's as seen through the eyes of a generation that lived through the Sexual Revolution. Creative baby boomers - including musician David Byrne, performance artist Spalding Gray, comedian Sandra Bernhard, radical activist Abbie Hoffman, and poet Allen Ginsberg - candidly recall their sexual coming-of-age tales in intimate interviews. Joyously campy and refreshingly carefree, "Heavy Petting" blends humorous, unbelievable footage of unhelpful sexed films with classic snippets of "The Wild One" and Elvis' hip gyrations, not to mention Bernhard talking about playing "doctor", always observant Ginsberg on a disastrous encounter with a girl, and Byrne on the childhood myths of masturbation. Eternal mysteries such as the female orgasm, the universal appeal of Marilyn Monroe, and the rituals of high school are laid bare by this lovable group of characters. [www.dvdempire.com]
Keywords: DVD-Video